2022
DOI: 10.2196/29118
|View full text |Cite
|
Sign up to set email alerts
|

Effective Communication of Personalized Risks and Patient Preferences During Surgical Informed Consent Using Data Visualization: Qualitative Semistructured Interview Study With Patients After Surgery

Abstract: Background There is no consensus on which risks to communicate to a prospective surgical patient during informed consent or how. Complicating the process, patient preferences may diverge from clinical assumptions and are often not considered for discussion. Such discrepancies can lead to confusion and resentment, raising the potential for legal action. To overcome these issues, we propose a visual consent tool that incorporates patient preferences and communicates personalized risks to patients usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, in preliminary studies previously conducted with adult patients, participants have largely rated personalized risk communication tools as easy to use [ 37 , 38 ], helpful [ 39 ], and beneficial to patients [ 40 ]. Participants believed that personalized risk communication might result in increased patient engagement [ 41 ], increased awareness and understanding of potential surgical complications, and deeper discussion with providers [ 42 ]. Participants who were presented with a personalized risk score while consenting for surgery, in particular, agreed that they had received adequate time discussing surgical risks, felt more comfortable with their procedure, had decreased anxiety [ 43 ], were significantly more satisfied with the consent process [ 40 , 43 ], and had increased knowledge about the risks associated with their surgery [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in preliminary studies previously conducted with adult patients, participants have largely rated personalized risk communication tools as easy to use [ 37 , 38 ], helpful [ 39 ], and beneficial to patients [ 40 ]. Participants believed that personalized risk communication might result in increased patient engagement [ 41 ], increased awareness and understanding of potential surgical complications, and deeper discussion with providers [ 42 ]. Participants who were presented with a personalized risk score while consenting for surgery, in particular, agreed that they had received adequate time discussing surgical risks, felt more comfortable with their procedure, had decreased anxiety [ 43 ], were significantly more satisfied with the consent process [ 40 , 43 ], and had increased knowledge about the risks associated with their surgery [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, patients also preferred the visual consent tool to text-based documents [ 42 ], found personalized surgical risk communication tools helpful for informed decision-making [ 39 ], indicated that they would use a personalized risk tool again before a future procedure [ 40 ], and believed sharing personalized risk information should be a universal requirement during surgical consultations [ 44 ]. Clinicians also highlighted that identifying modifiable risk factors was more important than nonmodifiable ones; thus, separating their contributions was critical [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity of the surgery, patients frequently have numerous queries regarding preoperative preparation, postoperative recovery, potential adverse events, and ongoing care of the surgical site. Sometimes, communication between the surgeon and patients may be lacking, resulting in inadequately informed patients who may be incapable of making enlightened decisions regarding their surgical care [9,10]. Such consultations can also be timeconsuming, potentially diverting surgeons and nurses from other responsibilities.…”
Section: Introductionmentioning
confidence: 99%